Optimization of Prostate Plan in a Pelvic Prosthesis Phantom - Dumela, Khombo Eunice (University of the Witwatersrand, Johannesburg, 2024)
Background: An increasing number of elderly prostate cancer patients with high-density material hip prosthesis are referred for external beam Radiotherapy (EBRT). Radiation treatment of pelvis cancer patients with high-density hip prosthesis needs special attention because of the artifacts created in the computed tomography (CT) field of view and the radiotherapy dosimetry challenges. The accuracy of the treatment planning dose calculation algorithms determines the accuracy of the dose delivered to the patient during radiation therapy. However, the most available algorithms do not accurately model the absorption of high-density metals’ scattering properties and underestimate the resulting dose perturbations. Aim: This study aims to optimize the dose distribution of prostate 3D conformal treatment, intensity-modulated radiotherapy (IMRT) and volumetric-modulated arc therapy (VMAT) in an in-house metallic hip prosthesis phantom. Methods and materials: In this study, an ionization chamber and Gafchromic (EBT3) films were used to physically measure the prostate point dose in an in-house pelvic phantom. The pelvic phantom was irradiated on the Linac with four static fields, namely, (1) anterior field, (2) posterior field, (3) right lateral field passing through the bone of the normal hip and (4) left lateral passing through the hip prosthesis. IMRT and VMATs plans were also generated on the phantom. The phantom was also irradiated with IMRT and VMATs plan. The use of single arc versus two arcs with avoidance sector were also evaluated. The phantom consists of different materials; Nylon-12 (a solid water-equivalent material) to simulate the prostate with a central cavity to accommodate an ionization chamber and film, superflab gel bolus to simulate human soft tissue, dental wax to simulate human soft tissue, bone anatomy for the right hip and a titanium implant to replace the bony structure of the left hip. For the static fields, an in-house pelvic phantom was simulated using the EGSnrc Monte Carlo code, and 6 and 15 MV photon energies were employed as in an experimental setting. The prostate point doses computed by the Treatment Planning System (TPS), measured using ionisation chamber, and Gafchromic EBT3 film were compared with the prostate point doses simulated by Monte Carlo code. Results and discussion: The novel phantom was constructed using superflab gel bolus, Nylon-12, dental wax, pig bone insert and a titanium alloy hip replacement. The radiological equivalence of the superflab gel bolus and dental wax was determined employing linear attenuation coefficients and then compared to an RW3 Solid water phantom. EGSnrc Monte Carlo (MC) code was used in this study. Before using Monte Carlo codes, they need to be validated by comparing the Linear accelerator Monte Carlo simulated dose distribution with the experimental data measured in a Linear accelerator using water and ionization chamber for 6 MV and 15 MV photon beams of different field sizes. The EGSnrc dose distributions were compared with the experimental measurements using a gamma analysis, employing a 2 %/2 mm distance-to-agreement criterion. The EGSnrc Monte Carlo calculated dose distribution agreed well with experimental measurements within 2 %. The MC beam model was then used to compute the dose distribution in an in-house pelvic phantom. The comparison of the measurements between the TPS calculated prostate point dose and ionization chamber for the 6 MV and 15 MV photon beams was: anterior (gantry 0°) 1.8 % and -0.5 %; posterior (gantry 180°) 1.7 % and -0.2 %; left lateral (gantry 90°) 6.3% and 4.2 %; right lateral (gantry 270°) -2.2 % and -2.1 % respectively. Results obtained for Gafchromic EBT3 film measured doses were: anterior 2.3 % and 1.3 %; posterior -0.9 % and 0.2 %, left lateral 4.5 % and 3.5 %; right lateral -2.1 % and -2.5%, for the 6 MV and 15 MV photon beams, respectively. Consequently, results obtained for comparison of TPS, ion chamber and Film with MC simulated doses were: anterior 3.9 %, -2.1 and -1.6% %; posterior 1.8 %, -0.1% and -2.7 %; left lateral -0.2 %, 6.5 % and 4.7 %; right lateral 0.4 %, -2.6% and -2.5 %, for the 6 MV photon beam. And for 15 MV photon beam the results were: anterior 1.9 %, -3.8 and -0.6%; posterior 2.0 %, -2.3 % and -2.2 %; left lateral 0.5 %, 3.7 % and 2.9 %; right lateral 0.4 %, -2.4 % and -2.9 %. Monte Carlo simulations and film measurements have a statistically significant difference of p<0.001, with the film measurements having a higher value than MC simulations except on the left lateral field. Monte Carlo simulations and ionization chamber measurements also show a significant difference of p<0.001, with the ionization chamber having a higher value than the MC simulation, except for the left lateral field passing through the hip prosthesis. The comparison of the measurements between the TPS calculated prostate point dose with ionization chamber and Gafchromic EBT3 film for the 6 MV IMRT plan of the beam passing through the prosthesis was 2.2 % and 3.3%, respectively. While the IMRT plan with avoided beam was 1.9 % and 3.1% for ionization chamber and Gafchromic EBT3 film, respectively. The comparison of the measurements between the TPS calculated prostate point dose for the 6 MV VMAT plan without avoiding for the beam passing through the prosthesis was 1.1 % and 2.2 % for ionization chamber and Gafchromic EBT3 film, respectively. While for VMAT plan with avoided sector as 3.0 % and 4.0% for ionization chamber and Gafchromic EBT3 film, respectively. The test suggested a significant difference of p=0.0001 between the distribution of film measurements and TPS calculated dose. Meanwhile, for ionization chamber measurements and TPS calculated dose; the test indicated a significant difference between ion chamber measurements and TPS calculated dose with a significant level of less than 0.001. in addition, MC simulated dose and TPS calculated dose; the test shows a percentage difference of -0.2 % and 0.5 % for 6 MV and 15 MV photon beams in the lateral field that passes through the prosthesis. The test indicated the significant difference of p=0.001 which is slightly lower compared to the other comparisons. Conclusion: The dual dosimetric pelvic prosthesis phantom is easy to assembly and is more convenient for second dose check for patients with hip prostheses. Through the use of the pelvic phantom, it was possible to measure the prostate point dose using ionization chamber and films. The TPS overestimated the prostate point dose because the treatment planning algorithm could not accurately determine the CT number and the electron density of the prosthesis due to the limitation on the CT scanner. The maximum deviation calculated in this study for TPS, ionization chamber Gafchromic EBT3 films when compared to Monte Carlo simulated dose comes from the lateral fields passing through the prosthesis for both 6 MV and 15 MV photon beams.
A thesis submitted in fulfilment of the requirements for the degree Doctor of Philosophy in Physics, to the Faculty of Science, School of Physics, University of the Witwatersrand, Johannesburg, 2024.
Keywords: In-house phantom; Ionization chamber; Gafchromic EBT3 film; 3D conformal; IMRT; VMAT; EGSnrc Monte Carlo code; UCTD; SDG-3: Good health and well-being; SDG-4: Quality education